New circumscription of the genus Gamochaeta (Asteraceae, Gnaphalieae) inferred from nuclear and plastid DNA sequences - Urtubey, Estrella (2016)
Gamochaeta (tribe Gnaphalieae, Asteraceae) is composed of ca. 60 species primarily distributed in tropical and subtropical America. Within the tribe Gnaphalieae, the genus is characterized by capitula arranged in spikes or head-like clusters, few hermaphroditic central florets, truncate style branches with apical sweeping trichomes, pappus bristles connate at the base into a ring falling as a unit, and achenes with globose twin trichomes. Previous molecular phylogenetic studies have suggested the paraphyly of the genus, but have not provided a basis for redefining generic limits due to incomplete taxon sampling. To address this problem, DNA sequences from the plastid (trnL-F) and nuclear (ETS and ITS) genomes were analyzed from a broad taxon sample representing the full range of morphological variation known in the genus. Our results affirm that Gamochaeta is paraphyletic as presently circumscribed. Two clades can be recognized: one clade that includes the majority of the species currently assigned to Gamochaeta and a second clade that includes Gamochaetopsis, Stuckertiella and seven species of Gamochaeta. We present here a new circumscription of Gamochaeta, including two new combinations, Gamochaeta alpina and Gamochaeta peregrina, and the resurrection of Gamochaeta capitata. Our results also show Omalotheca supina, O. norvegica and O. sylvatica, which were placed by some authors in Gamochaeta or in Gnaphalium, form a monophyletic group distantly related to both genera.